1998
DOI: 10.1046/j.1523-1755.1998.00758.x
|View full text |Cite
|
Sign up to set email alerts
|

Morphine modulates proliferation of kidney fibroblasts

Abstract: Renal interstitial scarring is an important component of heroin-associated nephropathy. Kidney fibroblasts have been demonstrated to play a role in the development of renal scarring in a variety of renal diseases. We studied the effect of morphine, an active metabolite of heroin, on the proliferation of kidney fibroblasts. Morphine at a concentration of 10(-12) M enhanced (P < 0.001) the proliferation of kidney fibroblasts (control, 67.5 +/- 2.0 vs. morphine, 112.2 +/- 10.1 x 10(4) cells/well). [3H]thymidine i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
0
5

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(60 citation statements)
references
References 25 publications
3
52
0
5
Order By: Relevance
“…While the rest are changed into active metabolites by the liver. Metabolites of the drug that are excreted via kidneys may also cause cellular damage leading to kidney dysfunction [24].…”
Section: Discussionmentioning
confidence: 99%
“…While the rest are changed into active metabolites by the liver. Metabolites of the drug that are excreted via kidneys may also cause cellular damage leading to kidney dysfunction [24].…”
Section: Discussionmentioning
confidence: 99%
“…At lower concentrations, morphine predominantly stimulates mesangial cell and fibroblast proliferation, mesangial matrix deposition, and macrophage activity. At higher concentrations, morphine inhibits mesangial cell and fibroblast proliferation, mesangial matrix deposition, and macrophage activity (185)(186)(187)(188)(189).…”
Section: Direct Effects Of Heroin/morphine On the Kidney: Pathophysiomentioning
confidence: 99%
“…They suggested that this effect was mediated through a neurotrophic mechanism or inhibition of neurotransmission (Meriney et al, 1985). Morphine also prevented peroxynitrite-induced apoptosis in primary astrocytes (Kim et al, 2001) and enhanced the proliferation of endothelial cells (Gupta et al, 2002), kidney fibroblasts (Singhal et al, 1998), and adult hippocampal progenitor neurons (Persson et al, 2003). In addition, dynorphin (KOR agonist) and DOR agonists were found to increase proliferation of prostate cancer cells (Moon, 1988), rat splenocytes (Ni et al, 1999), and neuroblastoma cells (Law and Bergsbaken, 1995;Law et al, 1997), respectively.…”
Section: Growth-promoting and Protective Effectsmentioning
confidence: 99%